Tanjung Lesung: A Natural Tourism Destination For The New Era Post-Covid-19 (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The United Nations World Tourism Organization (UNWTO) predicts that tourism visits which are estimated to be in the 20-30% range will decrease to 3% - 4% due to the COVID-19 pandemic (UNWTO: 2020). The COVID-19 pandemic has changed the acceleration in all aspects of life, especially changes in the lifestyle of the Indonesian people since the echo of the new normal era. Especially in the tourism sector, it needs fast recovery for innovations. The concept of natural tourism (open space) is an alternative to tourism in the new normal era. This condition encourages changes in tourist behavior to be able to adapt to the new normal. Natural Tourism Destinations are described in the attributes of attraction, accessibility, amenities, and ancillary. This study uses a descriptive qualitative method and the sampling technique used in this study was purposive sampling, with 100 respondents. Data analysis, perception consumer matrix mapping, and cartesian diagram. Based on the results in quadrant A, shows the sub-attributes of tourist attraction, Health Protocol Services, and Location. Sub-attributes in quadrant B are natural panorama, uniqueness of attractions, parking space, safety, tourist destination facilities, and promotions. In quadrant C there are varied attractions, track conditions, tourist information canters, and physical development. In quadrant D there are modes of transportation and cleanliness.